Analisis Kinetika Pertukaran Ion NH4+ dan H+ pada Zeolit Alam Lampung dengan Shrinking Core Model - Simparmin Ginting (Jurnal Rekayasa Kimia & Lingkungan)
Ion exchange process between ion NH4+ and H+ by using zeolite as its ion exchanger is one of methods to purify water from ammonium ion content. Natural zeolites are chosen as ion exchanger because it is abundantly provided in Indonesia, especially in Lampung. The influences of reaction temperature and stirrer speed toward reaction rate constant, mass transfer coefficient and effective diffusivity in batch ion exchange process, were analysed by using shrinking core model. Processes run by mixing zeolite and ammonium solution in a stirred tank at 30, 40 and 50oC with stirrer speed variation of 700, 800 and 900 rpm. Every 5 up to 60 min, the sample was taken for ammonium ion analyses. The results show that mass transfer, intraparticle diffusion and ion exchange reaction resistance influenced the overall rate of reaction. The results also show that reaction temperature and stirrer speed influenced the reaction rate constant, mass transfer coefficient and effective diffusivity. The correlations of them are stated in simple empirical equation. Shrinking core model was good to describe the ion exchange kinetics between NH4+ and H+ ion in natural zeolite from Lampung with the average error range of 1,15 % – 3,71%.